IDENTIFIKASI PERILAKU KURANG PERCAYA DIRI SISWA PADA SAAT MENYAMPAIKAN ARGUMEN DI KELAS DI SMP NEGERI 03 KOTA JAMBI - Rahmadan, Galih; Yanto; Sarman, Freddi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to identify behaviors of students who lack self-confidence when expressing arguments in class at SMP Negeri 03 Kota Jambi. This research employs a descriptive qualitative approach. Data collection techniques include observation, in-depth interviews, and documentation. The research involved four students with initials AR, M, TR, and L who demonstrated low self-confidence behaviors in the classroom, as well as the school counselor (BK) as a key informant. The results revealed that the self-confidence deficit behavior of students was influenced by several interrelated factors: negative self-concept, low self-esteem, unpleasant past experiences such as being ridiculed by classmates, and feelings of shame combined with a fear of failure. Students with a low self-concept tended to remain passive during learning activities, chose silence when teachers posed questions, and avoided speaking in front of the class. Low self-esteem caused students to feel inferior, unable to openly express opinions, and overly sensitive to negative evaluations from peers. Negative experiences, particularly being mocked when attempting to answer questions, significantly impacted the development of student self-confidence. The findings indicate that the school counselor plays a crucial role in providing individual counseling services, group guidance sessions, and positive motivation to help students become more confident and actively participate in conveying arguments in class. It is recommended that schools create a more supportive learning environment and involve school counselors more systematically in developing students social and communicative confidence. Keywords: self-confidence, argument, student behavior, guidance and counseling, qualitative research